Ang lalake sa Parola - Altarejos, Joselito; Del Rosario, Vic. (Quezon City Viva Video., 2007)
This story is a search for oneself as seen through the lens of rural homosexuality legends and fairies and the lies that men create to escape the bitter realities of this world.
VCD
Director, Joselito Altarejos ; executive producer, Vic Del Rosario
Harry Laurel, Jennifer Lee, Justin De Leon, Crispin Pineda
Keywords: Romance--Drama.